Sustainable economic development and growth: roles played by agglomeration economies on regional policy - Daisuke Nakamura (European Regional Science Association (ERSA), 2010)
The evaluation of economic development level is commonly measured by the growth rate of GDP. However, this single-dimensional measurement may cause potential issue to investigate sustainable economic development and growth model. An alternative framework is introduced to economic development analysis that includes the notion of growth feasible indicator (GFI). This indicator enables the examination to observe the potentiality of economic growth in the long run, which is normally hidden in the established model framework. The relationship between the GFI curve and public policy for sustainable development is also explored.
Keywords: D62; F12; O47; Q56; R58; 330; Economic development; growth theory; sustainable policy